2020
DOI: 10.1073/pnas.2004909117
|View full text |Cite
|
Sign up to set email alerts
|

Calcium flares and compartmentalization in rod photoreceptors

Abstract: Rod photoreceptors are composed of a soma and an inner segment (IS) connected to an outer segment (OS) by a thin cilium. OSs are composed of a stack of ∼800 lipid discs surrounded by the plasma membrane where phototransduction takes place. Intracellular calcium plays a major role in phototransduction and is more concentrated in the discs, where it can be incorporated and released. To study calcium dynamics in rods, we used the fluorescent calcium dye CaSiR-1 AM working in the near-infrared (NIR) (excitation at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…We used our spatially resolved phototransduction model [19] to perform simulations that showed that our conclusions remain valid when using a spatially resolved model (not shown). Recently, it has been found that the large outer segment of frog rods is a spatially inhomogeneous compartment [6, 35]. However, no such findings exist for mouse or primate rods and cones, which we focused on in this work.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…We used our spatially resolved phototransduction model [19] to perform simulations that showed that our conclusions remain valid when using a spatially resolved model (not shown). Recently, it has been found that the large outer segment of frog rods is a spatially inhomogeneous compartment [6, 35]. However, no such findings exist for mouse or primate rods and cones, which we focused on in this work.…”
Section: Discussionmentioning
confidence: 95%
“…We find a maximal sensitivity ratio around 2-3 between GCAPs −/− and WT photoreceptors for fast Ca 2+ kinetics. Because the observed sensitivity ratio between GCAPs −/− and WT photoreceptors is around 3 [34, 17, 52], this suggests that under physiological conditions the Ca 2+ kinetics is fast, and that the Ca 2+ concentration changes in proportion to the current [51, 60]. For step responses with an intermediate plateau phase, oscillations are visible during the initial and recovery phase of the response (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More precise and recent techniques such as atomic force microscopy, micropipettes, optical tweezers, magnetic tweezers, and uniaxial stretchers, have allowed great progress into mechanotransduction pathways studies (Huang et al, 2004;Chighizola et al, 2019) (Figure 5A). Amongst these methods, OT offers the advantage of being non-invasive, applying comparively large forces, being able to probe cells in a 3D scaffold environment and precisely measuring forces in 3D space (Nawaz et al, 2012;Capitanio and Pavone, 2013;Pontes et al, 2013;Arbore et al, 2019;Li et al, 2020). Very recently, Dagro et al (2019) used optically trapped silica beads to deform cell surfaces and measure their stiffness and elasticity.…”
Section: Mechanical Properties Of Neuronsmentioning
confidence: 99%